2015
DOI: 10.1002/jcp.25211
|View full text |Cite
|
Sign up to set email alerts
|

Appl1andAppl2are Expendable for Mouse Development But Are Essential for HGF-Induced Akt Activation and Migration in Mouse Embryonic Fibroblasts

Abstract: Although Appl1 and Appl2 have been implicated in multiple cellular activities, we and others have found that Appl1 is dispensable for mouse embryonic development, suggesting that Appl2 can substitute for Appl1 during development. To address this possibility, we generated conditionally targeted Appl2 mice. We found that ubiquitous Appl2 knockout (Appl2-/-) mice, much like Appl1-/- mice, are viable and grow normally to adulthood. Intriguingly, when Appl1-/- mice were crossed with Appl2-/- mice, we found that hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Immunoblots were prepared with 30–50 µg of protein lysate sample, as previously described (Tan et al, ). Antibodies used for immunoblotting included a pan‐Akt antibody (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblots were prepared with 30–50 µg of protein lysate sample, as previously described (Tan et al, ). Antibodies used for immunoblotting included a pan‐Akt antibody (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Our results here, together with our previous work (Broussard et al, 2012), indicate that APPL1 can be a negative regulator of cell migration, depending on the ECM substrate and the integrin repertoire (Figs 1 and 2). By contrast, other studies have reported that APPL1 is a positive regulator of migration (Tan et al, 2016(Tan et al, , 2010. There are some key differences between these studies that may explain the contradictory results, including the use of embryonic mouse cells (Tan et al, 2010) versus human cancer cells ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, whereas decreased internalization of α5β1 integrin leads to slower migration on FN, perhaps APPL1 also alters trafficking of the HGF receptor MET, which could lead to an increase in HGFinduced migration (Ménard et al, 2014;Muller et al, 2013). Tan et al (2016) also implicated APPL2 in cell migration, acting redundantly with APPL1. However, although APPL2 is expressed in HT1080 cells, a 50% knockdown of APPL2 alone, or in APPL1depleted cells, showed no effect on migration speed on FN (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as a crucial element of protein trafficking and cell signaling, APPL1 can mediate the Akt signaling pathway to augment various pathophysiological processes (Tan et al, 2016 ; Wang et al, 2016 ). Thus, based on our APPL1 and phosphorylated Akt results, we investigated whether the APPL1/Akt signaling pathway mediated the effect of curcumin on IR-induced AKI.…”
Section: Discussionmentioning
confidence: 99%